Chromosomal Instability in Farmers Exposed to Pesticides: High Prevalence of Clonal and Non-Clonal Chromosomal Alterations - Cepeda S; Forero-Castro M; Cárdenas-Nieto D; Martínez-Agüero M; Rondón-Lagos M (Dove Medical Press, 2020)
Sebastian Cepeda,1 Maribel Forero-Castro,1 Diana Cárdenas-Nieto,1 María Martínez-Agüero,2 Milena Rondón-Lagos1 1School of Biological Sciences, Universidad Pedagógica y Tecnológica de Colombia, Tunja 150003, Colombia; 2Biology Program, Faculty of Natural Sciences and Mathematics, Universidad del Rosario, Bogotá 111221, ColombiaCorrespondence: Milena Rondón-LagosSchool of Biological Sciences, Universidad Pedagógica y Tecnológica de Colombia, Tunja 150003, ColombiaTel/Fax +57-8-7405626Email sandra.rondon01@uptc.edu.coMaría Martínez-AgüeroBiology Program, Faculty of Natural Sciences and Mathematics, Universidad del Rosario, Bogotá 111221, ColombiaTel/Fax +57-1-297-0200 ext. 4029Email maria.martinez@urosario.edu.coIntroduction: An important economic activity in Colombia is agricultural production and farmers are frequently exposed to pesticides. Occupational exposure to pesticides is associated with an increased incidence of various diseases, including cancer, Parkinson’s disease, Alzheimer’s disease, reproductive disorders, and birth defects. However, although high genotoxicity is associated with these chemicals, information about the type and frequency of specific chromosomal alterations (CAs) and the level of chromosomal instability (CIN) induced by exposure to pesticides is scarce or absent.Methods: In this study, CAs and CIN were assessed in peripheral blood lymphocytes (PBLs) from five farmers occupationally exposed to pesticides and from five unexposed individuals using GTG-banding and molecular cytogenetic analysis.Results: A significant increase in clonal and non-clonal chromosomal alterations was observed in pesticide-exposed individuals compared with unexposed individuals (510± 12,2 vs 73± 5,7, respectively; p< 0.008). Among all CAs, monosomies and deletions were more frequently observed in the exposed group. Also, a high frequency of fragilities was observed in the exposed group.Conclusion: Together, these findings suggest that exposure to pesticides could be associated with CIN in PBLs and indicate the need for the establishment of educational programs on safety precautions when handling pesticides, such as wearing gloves, masks and boots, changing clothes and maintaining proper hygiene, among others. Further evaluation in other similar studies that include a greater number of individuals exposed to pesticides is necessary.Keywords: pesticides, occupational exposure, chromosomal instability, clonal chromosomal alteration, non-clonal chromosomal alteration